2019
DOI: 10.14254/2071-8330.2019/12-3/21
|View full text |Cite
|
Sign up to set email alerts
|

Controlling generation of family firms and earnings management in Indonesia: The role of accounting experts of audit committees

Abstract: This study aims to identify whether the controlling generation (founder vs. descendant) of family companies in Indonesia affects earnings management and analyze the role of accounting experts of audit committees in minimizing the implementation of earnings management. A total of 258 samples are collected from manufacturing group companies listed in the 2012-2017 Indonesian stock exchange. A modified Jones model is used as a proxy for earnings management. Results reveal that controlling by the first generation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
1
11
0
3
Order By: Relevance
“…The interests of families are closely related to the interests of the business, so that they would not be prone to managing earnings to avoid possible damage to the survival of the company and its reputation (Salvato and Moores, 2010;Borralho et al, 2020). Family firms who value SEW to a larger extent tend to avoid EM, which, if detected, would damage the reputation of the company and the family, putting at risk the survival of the firm for subsequent generations (Suprianto et al, 2019;Martin et al, 2016). Moreover, long-term focus limits pressure on a firm's management to achieve short-term performance goals, reducing the incentives for EM (Jiraporn and DaDalt, 2009).…”
Section: Earnings Management Rpts and Family Firmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interests of families are closely related to the interests of the business, so that they would not be prone to managing earnings to avoid possible damage to the survival of the company and its reputation (Salvato and Moores, 2010;Borralho et al, 2020). Family firms who value SEW to a larger extent tend to avoid EM, which, if detected, would damage the reputation of the company and the family, putting at risk the survival of the firm for subsequent generations (Suprianto et al, 2019;Martin et al, 2016). Moreover, long-term focus limits pressure on a firm's management to achieve short-term performance goals, reducing the incentives for EM (Jiraporn and DaDalt, 2009).…”
Section: Earnings Management Rpts and Family Firmsmentioning
confidence: 99%
“…, 2020). Family firms who value SEW to a larger extent tend to avoid EM, which, if detected, would damage the reputation of the company and the family, putting at risk the survival of the firm for subsequent generations (Suprianto et al. , 2019; Martin et al.…”
Section: Theoretical Framework Literature Review and Hypotheses Devel...mentioning
confidence: 99%
“…One of the unique characteristics of family companies is the emotional bond between family members who run the business (G omez-Mej ıa et al, 2007). Furthermore, a study by Suprianto et al (2019) found that family companies tend to maintain the good name of the family and focus on achieving company performance. Therefore, we believe that in non-family firms, accounting conservatism tends to affect the value relevance of the firm compared with family firms.…”
Section: Institutional Ownership and Value Relevancementioning
confidence: 99%
“…One explanation for these mixed findings is the agency costs incurred by the controlling shareholders (Lewellyn & Bao, 2021). The controlling shareholders of a family business tend to influence the actions and decisions of the managers (Brahmana, Setiawan, & Hooy, 2019;Setiawan, Aryani, Yuniarti, & Brahmana, 2019;Suprianto, Rahmawati, Setiawan, & Aryani, 2019), causing the managers to invest in low-return projects (Anderson et al, 2012;Choi et al, 2015;Brahmana et al, 2019;Yıldız et al, 2021).…”
Section: Moderating Role Of Controlling Shareholder On the Constraint...mentioning
confidence: 99%